CHALLENGES IN USING BLOCKCHAIN FOR SUPPLY CHAIN MANAGEMENT INFORMATION SYSTEMS - Muhammad Rizqi Nur; Luqman Hakim; Yusuf Amrozi (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2020)
Blockchain has been the hype in technology lately and supply chain management is often mentioned as one of its applications. However, it is unwise to just eat the hype. Blockchain does have weaknesses; some of its natures considered as strengths might be weaknesses or problems in some cases. There are many things to be considered and among them are the challenges. This paper presents a systematic literature review of challenges in using blockchain for supply chain management information systems. This paper aims to help stakeholders and top management of supply chains when considering on adopting blockchain. The literatures were gathered from open-access papers found on Google Scholar. A total of 76 unique papers were found and then 29 were selected. The findings were classified into 12 categories. The top three category of challenges are development and implementation, performance and efficiency, and sustainability and scalability. Apparently, although blockchain in cryptocurrency is pretty solid, there are many challenges in its usage for supply chain.